PERFORMANCE ANALYSIS OF BROILER IN CLOSED HOUSE AND OPENED HOUSE - Nuryati, Tutik (Jurnal Peternakan Nusantara, 2019)
The success of broiler production is expressed in the performance of broiler chickens. One of the achievements of broiler performance is influenced by management. Housing management factors have an important role as a determinant of the success of broiler farms. The purpose of this study was to analyze the performance of broilers in closed cages and open cages at Agricultural PPPPTK, Cianjur. The material used in the study was a closed house with a size of 10m x 20m with 3,000 birds and an opened house measuring 8m x 3m with 2,500 broiler chickens. The research design used was a completely randomized design with 2 treatments, namely closed cages and open cages and 3 repetitions of maintenance periods.The research method used is the observation method (direct observation in the field). The data used in the study are primary data and secondary data, are data on maintenance results of broiler chickens in closed cages and open cages at Agricultural PPPPTK in 2018 for 6 maintenance periods. The variables observed in this study were mortality, feed consumption, final body weight, feed conversion ratio (FCR), and performance index (IP). Data that has been observed, collected, then analyzed using the t test. The results showed that mortality, feed consumption, final body weight, FCR, and IP in closed house were respectively 13.07%; 2.53 kg / bird; 1.43 kg / bird; 1.78; and 213, while in opened house respectively 7.70%; 2.24 kg / bird; 1.38 kg / bird; 1.62; and 255. The performance of broiler chickens in open house is better than closed house. The performance of broilers in both types of house showed a low which was reflected in the low performance index, <300. Keywords: Broiler, Closed house, Opened house, Performance.